Doping effects on structural and magnetic properties of Heusler alloys Fe 2 Cr 1-x Co x Si - Liu, Yifan (2019)
In this work, 30nm Fe2Cr1-xCoxSi (FCCS) magnetic films were deposited on Cr buffered MgO (100) substrates by sputtering. Fe2Cr0.5Co0.5Si exhibits the largest magnetization and optimal ordered L21 cubic structure at in-situ annealing temperature (Tia) of 450°C. The Co composition dependence of crystalline structures, surface morphology, defects, lattice distortions and their correlation with the magnetic properties are analyzed in detail. The Co-doped samples show in-plane M-H loops with magnetic squareness ratio of 1 and increasing anisotropy energy density with Co composition. Appropriate Co doping composition promotes L21 phase but higher Co composition converts L21 to B2 phase. Doping effect and lattice mismatch both are proved to increase the defect density. In addition, distortions of the FCCS lattice are found to be approximately linear with Co composition. The largest lattice distortion (c/a) is 0.969 for Fe2Cr0.25Co0.75Si and the smallest is 0.983 for Fe2CrSi. Our analyses suggest that these tetragonal distortions mainly induced by an elastic stress from Cr buffer account for the large in-plane anisotropy energy. This work paves the way for further tailoring the magnetic and structural properties of quaternary Heusler alloys.